PENGARUH RENCANA PENGEMBANGAN JALAN LINGKAR TIMUR KAWASAN PERKOTAAN BUMIAYU KABUPATEN BREBES TERHADAP NILAI TANAH DI SEKITARNYA - , Masrumiyatun, Prof. Dr. Iswardono S. Permono, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Eastern ring road development plans in urban areas of Bumiayu increase accessibility to the surrounding community and give positive effects on economic growth in areas of south Brebes. Land price in a location will change if there are developments there. The development of land can be land distribution, changes in land contour, road construction, and paving, as well as other development carried out by people. The objective of this study is to analyze the effects of the eastern ring road development plans in the urban areas of Bumiayu on the surrounding land value. The data used in this study were latitude data for 40 transactions of lands and 80 NJOP in Bumiayu subdistrict, Brebes from 2008 to 2011. The study also examined the average value of land seen from two different conditions, i.e. before and after the eastern ring road development plans in the urban areas of Bumiayu. Results of the study showed that the dummy variables of transaction time, land size, and road width have significant and positive effects on land values, and the distance to CBD has negative effects on land value. The land value after the ring road development plans was in average higher than that before the ring road development plans. It was consistent with the theory that the price of land in a location will change if there is development there.